Can Employees Be Used to Overcome Independent Audit Limitations?. Issue 4 (7th June 2017) - Christopher, Joe; Leung, Philomena; Leong, Shane
Abstract: Independent financial statement auditors are appointed by shareholders to provide reasonable assurance on the reliability of financial statements published by management of reporting entities. However, in the last two decades questions have been raised concerning the credibility of external audits due to their apparent failure, especially following the spate of corporate collapses. This paper applies a critical review of literature and a multi‐theoretical governance perspective to examine the inherent limitation of independent external audits and argues that employees can contribute to reducing the limitation gap by strengthening governance through a structure that incorporates a board and employee management representation. It is argued that through this arrangement, auditors can benefit as they will be privy to additional information from employees about issues such as irregular matters that impact upon shareholders and other stakeholders, and control weaknesses across governance levels, allowing auditors to establish a broader understanding of organisational information that may otherwise be less readily available. Thus auditors can base their judgements in terms of audit risks, and develop audit plans based on more reliable information. The theoretical proposition emerging from these findings is that the traditional governance model should be refined to include employees as an additional component of governance. Abstract : This paper, through a synthesis and critical review of the literature, draws on a multi‐theoretical approach to governance to illustrate there is good reason to believe that the limits of external audits can be somewhat addressed by increasing employee involvement in corporate governance.